Pengaruh Kompensasi Terhadap Loyalitas Karyawan Dimediasi Kepuasan Kerja Pada PT. Tosari Utama Jayapura - Ambarak, Syafira Khairiyah; Husein, Sjamsiar (Universitas Yapis Papua, 2023)
This study aims to Compensate for Employee Loyalty Mediated by Job Satisfaction at PT. Tosari Utama Jayapura. The sample was taken using the opinion of Sugiyono (2017), namely saturated sampling or using the entire population as a sample, so that the total sample is 130 people. The analytical method used is mediation analysis with data processing tools using structural equation modeling (SEM) AMOS 24. The results show that compensation has a positive and significant effect on employee loyalty. Compensation has a positive and significant influence on employee job satisfaction. Job satisfaction has a positive and significant influence on employee loyalty. Job satisfaction can mediate the effect of compensation on employee loyalty at PT. Main Tosari.